Implementasi Teknologi Geolocation Pada Sistem Pelaporan Parkir Liar Berbasis Web - Prayata, Aldo Yusran; Romli, Moh. Ali (STMIK Banjarbaru, 2025)
This study is motivated by the low effectiveness of reporting illegal parking violations in urban and tourist areas, where the current manual reporting process often leads to delays in handling incidents and difficulties in accurately identifying the location. To address these issues, this research aims to develop an information system for reporting illegal parking based on web and mobile platforms by utilizing geolocation technology to make the reporting process faster, more accurate, and easier for the public to use. The system was developed using the Waterfall model, which includes the stages of requirements analysis, design, implementation, and testing using the Black-box method. It integrates the Google Maps API to automatically detect the reporter’s location and uses PostgreSQL as the main database for storing reports. The testing results indicate that all system features operate according to user requirements and accurately display incident locations, enabling more efficient reporting, assisting officers during verification processes, and supporting the digitalization of public services in the transportation sector.Keywords: Reporting System; Geolocation; API; Web Base AbstrakPenelitian ini dilatarbelakangi oleh rendahnya efektivitas pelaporan pelanggaran parkir liar di kawasan wisata dan perkotaan, di mana proses pelaporan yang masih dilakukan secara manual menyebabkan keterlambatan penanganan serta kesulitan dalam menentukan lokasi kejadian secara tepat. Untuk mengatasi masalah tersebut, penelitian ini bertujuan mengembangkan sistem informasi pelaporan parkir liar berbasis web dan mobile dengan memanfaatkan teknologi geolokasi agar proses pelaporan menjadi lebih cepat, akurat, dan mudah diakses oleh masyarakat. Sistem dikembangkan menggunakan model Waterfall yang meliputi tahap analisis kebutuhan, perancangan, implementasi, dan pengujian menggunakan metode Black-box. Sistem ini terintegrasi dengan Google Maps API untuk mendeteksi lokasi pelapor secara otomatis dan menggunakan PostgreSQL sebagai basis data penyimpanan laporan. Hasil pengujian menunjukkan bahwa seluruh fitur sistem telah berfungsi sesuai kebutuhan pengguna dan mampu menampilkan lokasi kejadian dengan akurat, sehingga sistem yang dibangun dapat meningkatkan efisiensi pelaporan, membantu proses verifikasi petugas, serta mendukung digitalisasi layanan publik di sektor transportasi.